2015
DOI: 10.1177/0886260515590787
|View full text |Cite
|
Sign up to set email alerts
|

“They’ll Always Find a Way to Get to You”: Technology Use in Adolescent Romantic Relationships and Its Role in Dating Violence and Abuse

Abstract: Electronic communication technology (ECT), such as mobile phones and online communication tools, is widely used by adolescents; however, the availability of such tools may have both positive and negative impacts within the context of romantic relationships. While an established literature has documented the nature, prevalence, and impact of traditional forms of adolescent dating violence and abuse (ADVA), limited empirical investigation has focused on the role of ECT in ADVA or what shall be termed technology-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
134
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 45 publications
(74 reference statements)
9
134
2
14
Order By: Relevance
“…Their frequent use of the communication technologies in their romantic relationships increases the possibility of expressing affection to their partners and being linked to them [9,10]. However, these technologies can also be used to stalk, harass and control current or former partners [7,8,[11][12][13][14][15]. It is estimated that between 12% and 56% of adolescents have experienced cyber dating violence victimization [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their frequent use of the communication technologies in their romantic relationships increases the possibility of expressing affection to their partners and being linked to them [9,10]. However, these technologies can also be used to stalk, harass and control current or former partners [7,8,[11][12][13][14][15]. It is estimated that between 12% and 56% of adolescents have experienced cyber dating violence victimization [16].…”
Section: Introductionmentioning
confidence: 99%
“…Cyber DV victimization is considered qualitatively different from victimization via offline dating violence because victims of such violence can be constantly attacked and feel unable to escape the situation [4,5,7,8,12]. Easy access to victims, lack of geographical boundaries and the rapid dissemination of victims' denigrating or humiliating information are characteristics of this type of violence that make victims feel increasingly helpless, which negatively impacts their well-being [4,[6][7][8]11,13,[24][25][26]. Information and communication technologies (ICTs) allow prejudicial information and images about victims to quickly spread to a very large audience, constant monitoring of their activity on social networks, and contact with them anytime and from anywhere [14,19,27].…”
Section: Introductionmentioning
confidence: 99%
“…19 A qualitative study with adolescents aged 12 to 18 years in the UK sought to explore the role of the use of technologies in their intimacy relationships. 20 These technologies can have a positive impact on the development and maintenance of relationships, but can provide a new pathway for unhealthy behaviors. They may also be perceived as less harmful than violence "in person".…”
Section: Discussionmentioning
confidence: 99%
“…They may also be perceived as less harmful than violence "in person". 20 Another US study with university students indicates that violence in intimate relationships lived in digital media is part of other violence. 21 In this sense, it alerts to the importance of describing these violence in the social contexts where they are experienced, in order to perceive where online experiences function as a "portent" of future violence.…”
Section: Discussionmentioning
confidence: 99%
“…This enables young people to control and monitor their partners more easily and with fewer restrictions (Van Ouytsel, Ponnet, et al, 2018). Qualitative research has also found that it is common for teenagers to share passwords at the beginning of a romantic relationship, as a sign of trust and commitment (Baker & Carreño, 2016;Bevan, 2017;Lucero et al, 2014), or that romantic partners demand each other's passwords (Stonard, Bowen, Walker, & Price, 2017). This can be an additional risk factor for online monitoring.…”
Section: Online Monitoring and Social Media Usementioning
confidence: 99%